Epigenetic Regulation of Macrophage Marker Expression Profiles in Kawasaki Disease - Guo, Mindy Ming-Huey; Chang, Ling-Sai; Huang, Ying-Hsien; Wang, Feng-Sheng; Kuo, Ho-Chang (Frontiers in Pediatrics, 2020)
Kawasaki disease (KD) is a common systemic vasculitides in children younger than 5 years of age. Activated macrophages are key drivers of vascular inflammation in KD. The aim of this study was to examine differences in M1 and M2 macrophage marker expression in patients with KD. Blood samples were obtained from 18 healthy controls and 18 patients with KD at 24 hours prior and 21 days after to intravenous immunoglobulin therapy. GeneChip Human Transcriptome Array 2.0 and Illumina HumanMethylation450 BeadChip were used to examined the mRNA expression and corresponding CpG site methylation ratios of 10 M1 surface markers and 15 M2 surface markers. Of the markers examined 4 M1 markers (IL1R1, TLR2, TLR4, IL2RA) and 10 M2 markers (IL1R2, ARG1, CCR2, TLR1, TLR8, TLR5, MS4A6A, CD36, MS4A4A, and CXCR1) showed increased mRNA expression in the acute phase of KD which decreased after IVIG therapy. (P<0.05) Corresponding CpG sites in the promoter regions these markers were hypomethylated in the acute phase of KD and significantly increased after IVIG therapy. In conclusion, both M1 and M2 markers showed increased mRNA expression in the acute phase of KD. CpG site methylation may be one of the mechanisms governing macrophage polarization in KD.